Dynamicuser-defined accesscontrol policies via programming language / Suzana Ahmad - Ahmad, Suzana (Institute of Graduate Studies, UiTM, 2018)
Allowing data sharing activities to the right users can be determined by concerned access control through assisting every attempt made by a user, to access a resource in an application system. The interests of authorized the users, who are protected by access control, can provide a safe, secure and accessible working environment. Implementation of access control involves three important issues, which include policies, models and mechanisms. The appointed administrator has the authorization to manage the access of data sharing under every possible circumstance by specifying the model of access control as high-level requirements for policy mechanisms. Commonly, most application systems rely on an administrator to manage access control policies which may lead to conflicts between users' and the administrator's empowerment. Such conflicts exist due to lack of involvement from endusers in handling the access control. Another issue raised, is those of unrevised services, which occur frequently due to massive and complex policy details that need to be handled by the administrator. Additionally, most programming languages and programming environments do not naturally support implementing policy for access control. Nevertheless, the policy needs to be coded as part of the system development for managing access control. Furthermore, access control policies are high-level features, which require high cost maintenance. This thesis examines the control mechanisms in data sharing activities among collaborative users. The results of the research undertaken offers a model that allows data owners to provision access control policies in collaborative data sharing environments via a specific programming language…